PENGETAHUAN PASIEN TENTANG PENYAKIT DEMAM BERDARAH DENGUE DI POLIKLINIK UMUM PUSKESMAS POASIA KOTA KENDARI - Taamu Taamu; Sitti Rachmi Misbah; Arif Purnama (Jurnal Kesehatan Manarang, 2017)
Dengue hemorrhagic fever is a disease caused by dengue virus that enter into human body through Aedes aegypti mosquito bites. Dengue Hemorrhagic Fever case in Southeast Sulawesi province from January to February 2016 has reached 530 cases with 3 deaths or 0,57%. This study aims to determine the description of patient knowledge about the causes, signs and symptoms, prevention and management of dengue fever. The sample in this research is obtained by accidental sampling technique as many as 82 people from the total population of 821 people who are patients in Public Health Center of Kendari Polyclinic. The results showed that the patient had sufficient knowledge of DHF on the aspect of cause as much as (43,9%), sign and symptom aspect as much (53,66%), prevention aspect as much (50,00%) while the management aspect, (45.12%). The conclusion of this study is that the majority of patients in the Public Polyclinic of Poasia City Health Center have sufficient knowledge on the causal aspects, signs and symptoms and preventive measures against dengue hemorrhagic fever. While in the management aspect of dengue hemorrhagic disease majority of patients have knowledge of good.